Natal maxillary primary molars: Case report - Galassi, Marlei Seccani [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Ramalho, Lizete Toledo Oliveira (My University, 2004)
An unusual case of a newborn with two immature natal maxillary molars is presented. Clinical and histological examination showed that the teeth were rootless and incompletely mineralized. The patient was followed up during one year and we confirmed that the natal teeth were from normal primary series.
Keywords: case report; clinical feature; deciduous tooth; family history; female; human; incisor; infant; molar tooth; mouth examination; orthodontics; tooth crown; tooth development; tooth extraction; tooth malformation; tooth radiography; treatment outcome; Female; Humans; Infant, Newborn; Maxilla; Molar; Natal Teeth; Tooth Extraction